The ACE Index: mapping childhood adversity in England. (27th December 2019) - Lewer, Dan; King, Emma; Bramley, Glen; Fitzpatrick, Suzanne; Treanor, Morag C; Maguire, Nick; Bullock, Miriam; Hayward, Andrew; Story, Al
Abstract: Background: Studies of adults show that adverse childhood experiences (ACEs) are associated with health and social problems and are more common among people living in deprived areas. However, there is limited information about the geographical pattern of contemporary ACEs. Methods: We used data from the police, social services, schools and vital statistics in England to calculate population rates of events that represent childhood adversity. We constructed an 'ACE Index' that summarizes the relative frequency of ACEs at local authority level, informed by the methods of the Index of Multiple Deprivation. We explored associations between the ACE Index and local characteristics in cross-sectional ecological analysis. Results: The ACE Index was strongly associated with the proportion of children that live in income-deprived households (child poverty). In addition, the ACE Index was independently associated with higher population density and was higher in certain regions, particularly the north-east. Conclusions: The association between ACEs and child poverty provides evidence of a process in which deprivation increases the risk of adverse experiences in childhood. The ACE Index can inform allocation of resources for prevention and mitigation of ACEs.